Atypical Retinal Phenotype in a Patient With Alström Syndrome and Biallelic Novel Pathogenic Variants in ALMS1, Including a de novo Variation - Mauring, Laura; Porter, Louise Frances; Pelletier, Valerie; Riehm, Axelle; Leuvrey, Anne-Sophie; Gouronc, Aurélie; Studer, Fouzia; Stoetzel, Corinne; Dollfus, Helene; Muller, Jean (Frontiers in Genetics, 2020)
Alström syndrome (ALMS) is a rare autosomal recessive multi-organ syndrome considered to date as a ciliopathy and caused by variations in ALMS1. Phenotypic variability is well documented, particularly for the systemic disease manifestations, however early-onset progressive retinal degeneration affecting both cones and rods (cone-rod type) is universal, leading to blindness by the teenage years. Other features include cardiomyopathy, kidney dysfunction, sensorineural deafness and childhood obesity associated with hyperinsulinemia and type 2 diabetes mellitus. Here we present an unusual and delayed retinal dystrophy phenotype associated with Alström syndrome in a fourteen-year-old female, with affected cone function and surprising complete preservation of rod function on serial electroretinograms. High throughput sequencing of the affected proband revealed compound heterozygosity with two novel nonsense variations in the ALMS1 gene, including one variant of de novo inheritance, an unusual finding in autosomal recessive diseases. To confirm the diagnosis in the context of an unusually mild phenotype and identification of novel variations we demonstrated the biallelic status of the compound heterozygous variations (c.[286C>T];[1211C>G], p.[(Gln96*)];[(Ser404*)]. This unique case extends our knowledge of the phenotypic variability and the pathogenic variation spectrum in ALMS patients.